Annual Report 2024: Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) - Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) is a project administered by the Alliance of Bioversity International and the International Centre for Tropical Agriculture (CIAT). Activities financed by the World Bank’s International Development Association (IDA) through AICCRA are undertaken by a broad coalition of partners working at continental, regional, and national levels. In In 2024, AICCRA reached 1.8 million smallholder farmers (approximately half of whom were women), providing access to climate-smart agricultural tools, technologies, practices, and services. Of these, more than 1.2 million individuals directly benefited by using the climate-smart agriculture (CSA) and climate information services (CIS) innovations they accessed. These outcomes, underpinned by strategic collaboration with a diversity of partners including national governments, regional bodies, private sector actors and more, have played an instrumental role in scaling climate resilience across diverse African communities.